2019
DOI: 10.3892/mmr.2019.10239
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide inhibits matrix metalloproteinases expression and osteoarthritis via the NF‑κB and Wnt/β‑catenin signaling pathways

Abstract: Osteoarthritis (OA) is a chronic joint disease involving cartilage erosion and matrix degradation. Costunolide is a sesquiterpene lactone that has been demonstrated to exert anti-inflammatory activities in a wide variety of cells. The aim of the present study was to investigate the effect of costunolide in OA treatment, using rat chondrocytes and an OA rat model, in which animals were subjected to destabilization of the medial meniscus. The results revealed that costunolide (2–6 µM) had no effect on chondrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The pharmacokinetic profile of costunolide has been reported [8] and its therapeutic potential is supported by numerous animal studies. Costunolide possesses anti-angiogenic [9,10] and -osteoarthritic effects [11]. It inhibits pulmonary [12] and hepatic fibrosis [13], induces hair growth [14] and shows strong larvicidal activity [15].…”
mentioning
confidence: 99%
“…The pharmacokinetic profile of costunolide has been reported [8] and its therapeutic potential is supported by numerous animal studies. Costunolide possesses anti-angiogenic [9,10] and -osteoarthritic effects [11]. It inhibits pulmonary [12] and hepatic fibrosis [13], induces hair growth [14] and shows strong larvicidal activity [15].…”
mentioning
confidence: 99%
“…) and ADAMTS5 are regarded as the key enzymes in the progression of OA that involves the breakdown of the ECM (31). Compared with respective control groups, the mRNA expression of ADAMTS5, MMP9, MMP13, PHD1, PHD2 and PHD3 in chondrocytes of BA-treated groups were significantly downregulated (P<0.01; Fig.…”
Section: Ba Downregulates Mmp9 Mmp13 Adamts5 and Prolyl Hydroxylasementioning
confidence: 88%
“…NF- κ B signaling pathway plays an important regulatory role in the occurrence and development of OA through maintaining the chondrocyte phenotype and balancing cartilage matrix metabolism [ 1 , 32 , 33 ]. Xue et al [ 34 ] have confirmed that LDC067 exerted protective effects in OA by inhibiting the NF- κ B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%